FDG PET/CT in clinical oncology: Case based approach with teaching points - Mihailovic, Jasna (Springer Berlin Heidelberg, 2012)
FDG PET/CT has rapidly emerged as an invaluable combined imaging modality that can identify tumors on the basis of not only anatomical alterations but also metabolic activity, thus allowing the detection of lesions that would otherwise be too small to distinguish. This book, comprising a collection of images from oncology cases, is organized according to the role of FDG PET/CT in the evaluation and management of oncology patients, and only secondarily by organ or tumor entity. In this way, it reflects the issues that clinicians actually address in their daily practice, namely: identification of an unknown or unsuspected primary; determination of the extent of disease; evaluation of response to therapy; and surveillance after response, i.e., detection of recurrent disease. In total, 100 cases involving different primary tumors are presented to illustrate findings in these different circumstances. FDG PET/CT in Clinical Oncology will be of great value to all newcomers to this field, whether medical students, radiology, nuclear medicine, or oncology fellows, or practicing physicians.